Energy storage enhancement of LixMn1.8Ti0.2O4@N-doped graphene oxide in organic and ionic liquid electrolytes (2023)
ABSTRACT: Spinel-type Li1-xMn2O4 material is a promising positive electrode material for lithium-ion batteries. This material presents 3D diffusion channels through the structure, allowing for the rapid diffusion of lithium ions during charge/discharge processes. Given its relevant properties, such as a theoretical specific capacity of 149 mA h g−1 and high working potential, we propose LixMn1.8Ti0.2O4@N-doped graphene oxide (x ≤ 1) as a superior positive electrode material for lithium-ion battery applications. In organic media, the spinel showed excellent Li storage performance due to the incorporation of a conductive carbonaceous matrix (using 1,10 phenanthroline as a graphene precursor). We obtained a specific capacity of 139 mA h g–1, which represented 81% charge retention after 70 cycles. Furthermore, taking advantage of the high working potential of this material, we studied the Li storage capacity using ionic liquids as electrolyte solvents. High rate cycling at high temperatures is essential for their practical applications in extreme environments. In this work, we performed rate capability experiments at different temperatures, obtaining the best response at 40 °C with a specific capacity of 117 mA h g–1 at an applied current density of 1 C.